Characterization and Classification of Some Typical Cotton-growing Soils of Samudrapur Block of Wardha District, Maharashtra - K. Karthikeyan (Journal of the Indian Society of Soil Science, 2022)
Detailed field survey (1:10,000 scale) was carried out using a base map prepared from satellite data(ALOS-DEM and Sentinel 2A data) and digital elevation models (DEM) in conjunction with Survey ofIndia (SOI) toposheets of 1:50,000 scale in Samudrapur block, Wardha district of Maharashtra. On thebasis of different soils from different landforms, seven soil series were identified in Samudrapur block.These seven soil series lies in the four major landforms i.e., Pediment, Upper Pediplain, Middle Pediplainand Valley which occupies 93.4% of total geographical area. The typifying pedons are very shallow to verydeep and their per cent sand, silt and clay ranged from 0.8 to 81.6, 0.4 to 39.1 and 6.2 to 73.4%,respectively. These pedons were neutral to strongly alkaline (pH 6.40-8.90), non-saline with low to mediumorganic carbon (0.04-0.91%) content, low to moderate calcium carbonate (1.31-5.66%) and high cationexchange capacity [>35 cmol(p+)kg-1]. The exchangeable complex of these pedons were dominated by Ca2+followed by Mg2+, Na+ and K+ cations with high base saturation (72.0-116%). Soils were classified asVertic Haplustepts, Typic Haplusterts, Lithic Ustorthents, Typic Haplustepts, Leptic Haplusterts, LithicHaplustepts and Sodic Haplusterts.